Tourism and resilience - Butler, Richard (CABI Publishing, 2017)
Introduction / Richard Butler -- The development of resilience thinking / Marta Berbés-Blázquez and Daniel Scott -- Community tourism resilience : some applications of the scale, change and resiliene (SCR) model / Alan A. Lew, Tsung-chiung Wu, Chin-cheng Ni, Pin T. Ng -- Socio-ecological balance in community based tourism experiences : a resarch proposal / Esteban Ruiz-Ballesteros -- Resilience and destination governance / Valerie A. Sheppard -- Resilience and destination governance : Whistler, B.C. / Valerie A. Sheppard -- Sri Lankan tourism development and implications for resilience / Jeremy Buultjens, Iraj Ratnayake, Athula Chammika Gnanapala -- Resilience, tourism and disasters / Susanne Becken and Bijan Khazai -- Resilience and perceptions of problems in alpine regions / Bruno Abegg, Robert Steiger and Lisa Trawöger -- Tourism resilience in UK national parks / Janet Cochrane -- Resilience and protected area tourism in Purnululu National Park : understanding interactions with a focus on community benefits / Jennifer Strickland-Munro -- Resilience and tourism in islands : insights from the Caribbean / Arjen Alberts and Godfrey Baldacchino -- Resilience and tourism in remote locations : Pitcairn Islands / Maria Amoamo -- Issues of resilience, sustainability and responsibility in tourism / Harold Goodwin -- Betting on casino tourism resilience : a case study of casino expansion in Macao and the Asia region / Glenn McCartney -- Resilience as new political reality / Jonathan Pugh -- Conclusions / Richard Butler
Includes bibliographical references and index
Enthält 17 Beiträge
Keywords: Nachhaltigkeit; Tourismus